A survey on dogs with valvular disease flying to Japan for operation - Arane Takahashi; Sayaka Takeuchi; Ayaka Chen; Masami Uechi (Scientific Reports, 2023)
Abstract In small-breed dogs, myxomatous mitral valve disease (MMVD) is a common disease which may lead to chronic heart failure. Mitral valve repair is an optimal surgical treatment that is currently available in limited veterinary facilities globally because it requires a special surgery team and specific devices. Therefore, some dogs must travel overseas to undergo this surgery. However, a question arises regarding the safety of dogs when traveling by air with a heart disease. We aimed to evaluate the effect of flight journey on dogs with mitral valve disease, including survival rates, symptoms during the trip, laboratory test results, and operational outcomes. All dogs stayed near the owner in the cabin during the flight. The survival rate after the flight was 97.5% in 80 dogs. The surgical survival rates (96.0% and 94.3%) and hospitalization periods (7 days and 7 days) were similar between overseas and domestic dogs. This report shows that taking air flights in the cabin may not have a significant effect on dogs with MMVD, on the premise that their overall conditions are stable under cardiac medication.